Pengaruh Minat Dan Tingkat Harga Terhadap Preferensi Masyarakat Muslim Yang Akan Menggunakan Akad Murabahah Pada KPR Bank Syariah Di Kota Jambi - Natasha Aurora Geraldine; Paulina Lubis; Ary Dean Amri (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to determine the description of interest, price level, and preference of Muslim community using murabahah contract on KPR Bank Syariah in Jambi City, analyze the influence of interest, price level on the preference of Muslim community using murabahah contract on KPR Bank Syariah in Jambi City partially, and analyze the influence of interest and price level on the preference of Muslim community using murabahah contract on KPR Bank Syariah in Jambi City simultaneously. The population in this study was 412,850 residents of Jambi City who are Muslim and are included in the productive age category. The analysis method in this study is quantitative data analysis technique. The results of the research that has been conducted: 1) Public interest in Murabahah contract in KPR Bank Syariah is moderate. This shows that people are starting to realize the importance of sharia-based financing, but have not fully made it their main choice. 2) Price level has a significant influence on public preference in choosing Murabahah contract. 3) Interest does not have a significant effect on preference. 4) Interest and price level influence the preference of Muslim community to use murabahah contract on KPR Bank Syariah in Jambi City simultaneously.